Crack onset and propagation at fibre–matrix elastic interfaces under biaxial loading using finite fracture mechanics. (March 2016) - Muñoz-Reja, M.; Távara, L.; Mantič, V.; Cornetti, P.
Abstract: A new fracture criterion able to predict crack onset and propagation at interfaces between solids is formulated, implemented in a computational code and applied to a particular problem in composites on a microscale. More specifically, this criterion is used to study the debond onset and propagation in mixed mode in the case of a single fibre subjected to a biaxial remote loading. The fracture criterion formulation is based on the Linear Elastic-(Perfectly) Brittle Interface Model (LEBIM) combined with a Finite Fracture Mechanics (FFM) approach, where the stress and energy criteria are suitably coupled. Each of these criteria is a necessary but not sufficient condition for crack onset and propagation. Two empirical mixed-mode fracture criteria are considered and tested: the interface fracture toughness law by Hutchinson and Suo and the quadratic stress criterion. The FFM + LEBIM approach developed offers an adequate characterization of the interface stiffness in contrast to the too restrictive, original LEBIM formulation.